Christianity and modernity in Eastern Europe - Berglund, Bruce R.; Porter, Brian (Central European University Press, 2010)
"This is a path-breaking book in two different ways. It contributes to the re-evaluation of the nature of modern European religion generally, and to the nature of religion in the modern world."